AV nodal ablation in atrial fi brillation - Obel, I.W.P. (SA Heart Journal, 2017)
Atrial fibrillation has reached epidemic proportions and is associated with important increases in mortality and morbidity. This increased risk is most prominent in patients with heart failure. Apart from anticoagulation, therapeutic approaches are: attempts (mainly pharmacological) at rhythm control (attainment and preservation of sinus rhythm) or rate control, which focuses on attaining an acceptable ventricular rate. The latter can be reliably and easily attained by ablation of the AV node and pacing. Long-term (up to 120 months) results of AV nodal ablation and pace are reviewed in 147 patients with NYHA Grade III or IV heart failure and atrial fibrillation and presented. This analysis indicates that AV node ablation is an effective form of therapy since prognosis after AV node ablation relates entirely to the underlying illness and not the atrial fibrillation